Phenological diversity of freshwater migration can prolong assemblage‐level migration period in amphidromous fishes in a temperate river system in Japan. Issue 3 (11th May 2020) - Tanaka, Ryosuke; Hirashima, Kentaro; Kunishima, Taiga; Uno, Hiromi; Sato, Takuya
Abstract: Animal migration mediates many ecological processes by transferring materials and organisms across ecosystems. Migration period in each species is often limited in relatively short‐term. However, interspecific variations in migration phenology may prolong migration period at assemblage‐level. In this study, we tested (a) whether and how much degree the timing and duration of freshwater migration differ among amphidromous fish species; (b) in what extent the species diversity prolongs the assemblage‐level migration period. Diverse amphidromous species migrated up the studied river system (Arida River, Japan), with species‐specific migration timing and duration. The large variation in the peak time of migration was found among species within a genus; that is, more than 2‐month difference among four Rhinogobius species. In addition to the within‐genus variation, there was much higher variation across genera (≈4‐month difference in maximum in Sicyopterus japonicus vs. Rhinogobius nagoyae ). Collectively, we observed migrating fish over 10 months from March to December in Arida River. The species diversity positively and nonlinearly increased the assemblage‐level migration period, suggesting the importance of species diversity on prolonging resource transfer from marine to freshwater ecosystems. Abstract : Diverse amphidromous fishes migrated up a river ecosystem, with species‐specific migration time and duration. This suggested the importance of species diversity on prolonging resource transfer from marine to freshwater ecosystems.